58 What support do care home residents need from community specialist palliative care?. (14th March 2023) - Davies, James; Capel, Margred; Rawlinson, Fiona; Gazi, Terri; Rees, Susan
Abstract : Objectives: City Hospice is a community specialist palliative care (SPC) team caring for the population of Cardiff (372, 000). A service evaluation was undertaken to review the scope of SPC input required for residents referred from care homes (residential and nursing homes). Methods: A mixed method evaluation was undertaken for all patients from care homes referred between 1st January 2019 and 31st December 2020. Key themes of the required input from the SPC team at first assessment were analysed by 2 Palliative Medicine Consultants. Data including demographics was entered into a Microsoft Excel spreadsheet, and statistical analysis performed. Results: 272 referrals (12% of total referrals) were from care homes during the specified time period, the majority with a non-malignant diagnosis (67%). 42 residents (15% of those referred) were not reviewed, dying from an acute deterioration before initial assessment. 81% of residents reviewed were deemed to have SPC needs, with only 5% of residents being discharged at first assessment. The main SPC needs identified at first assessment fell into the following categories: recognition of deteriorating condition; symptom control including ordering subcutaneous anticipatory medications in 69% of residents; Advance Care Planning (ACP) including DNACPR decisions in 89% of residents, establishing preferred place of death (PPD) in 94% of residents and completion of an ACP document in 58% of residents; facilitation of communication; supporting care home staff. Conclusions: Community SPC teams have an important role in supporting residents, care home staff and primary care in delivering high quality palliative care to care home residents approaching the end of life. This service evaluation has highlighted that the majority of care home residents have SPC needs and highlights the key themes of need. Meeting these needs resulting in achieving PPD in 96% of nursing home and 88% of residential home residents.